Bagaimana Al-Qur’an menjawab kebingungan remaja dalam menentukan tujuan hidup - Nabila, Syarifah (Maliki Interdisciplinary Journal, 2023)
Determining the right foundation for life goals as a provision for happiness in the present and in the future is the main thing. This article aims to discuss psychological problems in the form of confusion about the purpose of life experienced by adolescents with the solutions offered by the Qur’an. The research method used is qualitative with primary source literature in the form of the Al-Qur’an and the book of commentaries on Ibn Kathir along with secondary sources in the form of journal articles, books and other scientific works. The results and discussion of the research is that the phase of adolescents who experience confusion about the purpose of life indicates that there is a psychological gap within them. Through humanistic psychological theory, this phenomenon is proven to be true. Then the Qur’an, since it was first revealed, has provided explanations aimed at all humans from time to time. In answering questions about the purpose of life, through the Qur’an Allah SWT has advised QS. Adz Dzariyat: 56 and QS. Al-Baqarah: 30. That the main task of humans on this earth is only to worship Allah SWT and maintain this earth with the provision of the best potential from Allah SWT. The task is defined as a vision of life that accompanies life while in the world. Confusion about the purpose of life indicates that there is a good start to human development. The function of the Qur’an is to provide proper knowledge for the emptiness of the human soul and make it the best version of youth.